THE INFLUENCE OF STRAIGHT OUTTA COMPTON’S SLANG ON DAILY CONVERSATION OF COLLEGE STUDENTS - Pedro, Jose Candra (ENGLISH JOURNAL, 2022)
It is undeniable that literary works such as films, novels, comics or any other literary works can affect the life of someone who enjoys literary works. From that it can influence people in any ways. One of them is the film Straight Outta Compton which tells about hip hop culture with their music and stories about life in their neighborhood, where slang is integrated into their everyday language. The aims of this study are to investigate the types of Straight Outta Compton’s slang words used by college students in daily conversation, social function of the slang and the influence of the slang in daily life. This study referred to the theory of types of slang by Allan and Buridge (2006), social function of slang by Zhou and Fan (2013), and the influence of slang by Mazer and Hunt (2008). This study employed descriptive qualitative method in which the data were elaborated descriptively from careful analysis. Observation and interview were applied to collect the data. The participants of the study were 7 college students from different universities in Surabaya. The results of this study revealed that there are 12 slang words in which clipping is the most common type of slang words used by college students, the study also showed that social function of slang that often used by college students is emotive feelings and lastly, the result of the study showed that there are positive and negative influences of using the slang words, where the positive side appears more.